Estudo do efeito da temperatura na rugosidade e potência de corte no processo de torneamento a quente - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Machining is classified as a manufacturing process in which material removal occurs, giving shape and finish to the machined part. The metallurgical industry has been evolving over the years with the creation of the machine tool, which facilitates the removal of material, known as agglomerate. In the turning process, various difficulties are encountered related to the hardness of the material which can cause surfasse defects due to residual stresses, cracks, excessive surface roughness and losses in the fundamental properties of the metal. In order to improve the problems encountered, the hot spin was performed with external heat sources in which the part was heated in an electric oven and subsequently maintained its temperature with electrical infrared electrical resistors to improve its machinability. This procedure improved chip removal as well as reducing the specific power consumption used by the winch to carry out the process, taking up little space and being considered under its cost of acquisition. The reduction of the energy consumption presented the best performances at the temperature of 200 ° C, as well as the values obtained for surface roughness and chip generation.
Keywords: Engenharia mecânica; Torneamento; Aspereza de superfície; Usinabilidade; Mechanical Engineering; Surface roughness; Turning; Machinability; CNPQ::ENGENHARIAS